TWO YEARS IN THE DEVELOPMENT OF A NEW INTERDISCIPLINARY PEDIATRIC CHRONIC PAIN PROGRAM: OPPORTUNITIES, INITIATIVES, AND CHALLENGES. (18th May 2018) - Edwards, Kim; Elik, Nez; McMurtry, C Meghan; Findlay, Sheri; Rodrigues, Allison; Kattailr, Deepa
Abstract: BACKGROUND: "…The field of paediatric pain medicine has demonstrated the benefits of interdisciplinary collaboration more than any other endeavour" (Law, Palermo, & Walco, 2013). Recently, the Ontario Ministry of Health and Long-term Care announced the funding of specialty paediatric chronic pain programs in several children's hospitals across the province of Ontario, including McMaster Children's Hospital. The Pediatric Chronic Pain Program includes Physicians (Pediatricians, Psychiatrist, Anesthesiologist), Psychologists, Child Life Specialist, Registered Nurse, Nurse Practitioner, Occupational Therapist, Physiotherapist, Social Workers, Pharmacist, and a Clinical Manager. OBJECTIVES: The purpose of this poster is to highlight new initiatives within our clinic, including the development of a pain education session for families, group treatments (e.g., a 5 week Rise Above Pain Group; a 5-week Parenting Group), and a research database (to allow for program evaluation integrated within our clinical work). DESIGN/METHODS: Challenges in developing a new clinic/new programs and providing care to complex families (e.g., professional roles and competencies, diagnostic discrepancies) will be discussed. CONCLUSION: Implications for program development in new and established clinics will be highlighted.